Opioids in the management of persistent non-cancer pain. Issue 10 (October 2019) - Yamanaka, Shun; Miller, Lucy
Abstract: One in five Europeans suffers from persistent pain which, for the majority, is non-oncological in origin. Patients with persistent non-cancer pain (PNCP) are a heterogeneous group in whom there is significant biological, psychological and societal comorbidity. Recently, there has been a large increase in opioid prescribing for PNCP, despite its limited evidence base and adverse side effect profile, including opioid dependence. This review examines the effectiveness and safety of long-term opioids in PNCP, as well as current best practice guidelines on the initiation, monitoring and titration of opioids in the out-patient setting.